Isolation and evaluation of a Bacillus altitudinis strain to improve cigar tobacco leaves fermentation - Liu, Hejun; Fang, Xin; Guo, Shiping; Zhang, Bo; Wu, Chongde; Zhong, Qiu; Zhang, Ruina; Shi, Hongzhi; Qin, Yanqing; Zeng, Shuhua; Jin, Yao (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionHigh levels of nitrogenous compounds such as proteins and alkaloids in cigar tobacco leaves can negatively impact combustion, smoke smoothness, and overall sensory quality. At the same time, the formation of aroma-active compounds during fermentation is essential for desirable flavor development. This study aimed to isolate a functional bacterial strain capable of accelerating nitrogen compound degradation and enhancing aroma quality through bioaugmented fermentation.MethodsA total of 65 bacterial strains were isolated from naturally fermented cigar tobacco using a tobacco extract-based medium. Sixteen showed significant protease activity, and Bacillus altitudinis (CCTCC M20211370) was selected for further study. Laboratory- and industrial-scale fermentation trials were conducted with this strain. Volatile compounds were analyzed using gas chromatography–mass spectrometry (GC-MS), microbial community dynamics were assessed via high-throughput sequencing, and sensory evaluations were performed to assess quality improvements.ResultsInoculation with Bacillus altitudinis significantly increased desirable aroma compounds such as neophytadiene and β-ionone, while reducing harmful compounds including nicotine and myosmine. The microbial structure was reshaped, with enrichment of beneficial genera like Bacillus and Oceanobacillus. Sensory analysis confirmed improved aroma complexity, featuring enhanced floral, honey-sweet, and resinous notes.DiscussionBacillus altitudinis effectively improved cigar tobacco quality by promoting nitrogen compound degradation and modulating microbial metabolism to enhance aroma development. These findings support its potential as a bioaugmentation agent in industrial cigar fermentation. Further genomic and enzymatic studies are warranted to elucidate its functional mechanisms and facilitate large-scale application.